Drone – A Tool of Modern Teror (London Journal of Research In Humanities and Social Sciences, 2024)
In our reality, an Unmanned Aerial Vehicle is not only a useful technology used in the military or commercial environment, but also poses a kind of threat to many areas of functioning of modern society. It is concluded that there may be some possibilities of deliberate, terrorist use of drone technology. Low cost, easy access to drone technology on commercial markets creates an excellent opportunity to purchase drones for all types of groups, both state and non-state entities. Terrorism is as old as humanity and is associated with a person 's willingness to use violence for individual gain or political power. The question therefore arises: is this threat still imminent? The revolutionary development of artificial intelligence (AI) and drone technology poses a serious threat to humanity and has the potential to automate the killing process on a massive scale. These technologies may provide terrorist groups with the opportunity to acquire, develop deadly autonomous weapons, or create "killer robots", which would dramatically increase their ability to create incidents of mass destruction of cities, especially in the group of Western countries. The Case Study of DAESH activity shows the process of home-based efforts to master drone technology and thus & quot; transfer" the use of terrorist attacks to a higher level.
Keywords: satisfaction with learning; english for effective communication course; and course content.; Unmanned Aerial Vehicle; Drone Technology; Terrorism; Case Study of Drone Terrorism DAESH